PENGGUNAAN NOMINE DALAM PASAR MODAL: ASPEK HUKUM DAN IMPLIKASI TERHADAP KEPASTIAN HUKUM BAGI INVESTOR - Anggun, Rizku Fouriza; Gultom, Elfrida Ratnawati; Rahmawan, Dhany; Indirahati, Novina Sri; Bustani, Simona (Ensiklopedia of Journal, 2025)
Abstract: This study examines the practice of nominee agreements in Indonesia's capital market, which, while offering flexibility to foreign investors, poses significant legal risks for the involved parties. The analysis focuses on the potential legal impacts, implications for legal certainty, and transparency challenges arising from such agreements. Findings reveal that nominee arrangements often violate Article 33 of Law No. 25 of 2007, leading to nullification and detriment to beneficiaries who lack legal recognition. Additionally, the practice creates loopholes for tax evasion and money laundering, undermining market integrity. The study recommends strengthening regulations through technologies like blockchain, stricter law enforcement, and the adoption of beneficial ownership principles to enhance transparency. These reforms aim to make Indonesia's capital market more competitive, secure, and reliable on an international scale. This research serves as a vital reference for policy development and legal system improvement in capital market governance. Keywords: Capital Market, Investors, Nominee agreement